PENINGKATAN SUMBER PENDAPATAN MASYARAKAT DESA SOROPIA KECAMATAN SOROPIA KABUPATEN KONAWE MELALUI PELATIHAN PEMBUATAN BAKSO AYAM - Badaruddin, Rusli; Pagala, Muhammad Amrullah; Nafiu, La Ode; Malesi, Rahman La; Libriani, Restu; Munadi, La Ode Muh (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Community service activities carried out by a team of lecturers from the Faculty of Animal Husbandry integrated with the Thematic KKN program from the Research and Community Service Institute (LPPM) of Halu Oleo University in 2024 were carried out in Soropia village, Soropia sub-district, Konawe district. Introducing post-harvest livestock meat processing techniques into chicken meatballs to the Soropia village community. This is intended to increase community creativity in processing food ingredients and become a source of income. Community service activities in Soropia village were carried out in two stages. The first stage is a village community meeting regarding the delivery of work programs. Furthermore, the second stage is the demonstration stage of making meatballs. Meatball processing in principle consists of four stages, namely, crushing, grinding meat, making dough, molding meatballs and cooking and packaging. The output achieved in this activity is an increase in the insight and knowledge of the Soropia village community regarding post-harvest livestock processing.